Improvement of Glycogenic Hepatopathy With Minimal Corresponding Improvement of Glycemic Control in a Person With Type 1 Diabetes: Case Report and Literature Review - Joselyn Tessa Tonleu, BS; Nicolas A. Reyes, MD; Natalie D. Hillerson, MD; William B. Horton, MD, MSc, FACP (AACE Clinical Case Reports)
Background/Objective: Glycogenic hepatopathy is characterized by diffuse glycogen accumulation in hepatocytes that leads to hepatomegaly and elevated transaminases. Notably, the condition is reversible as improving glycemic control has been shown to resolve glycogenic hepatopathy and provide symptomatic relief. Case Report: A 30-year-old female with longstanding and poorly-controlled type 1 diabetes presented to her primary care physician for a routine follow-up visit. Routine lab work demonstrated hyperglycemia and elevated liver enzymes (alkaline phosphatase of 180 U/L, aspartate aminotransferase of 111 U/L, and alanine aminotransferase of 101 U/L). At laboratory reassessment 3 weeks later, liver function tests remained elevated and hepatic ultrasound was unrevealing. She was referred to gastroenterology for further evaluation and laboratory tests for viral and autoimmune hepatitis were negative while magnetic resonance imaging of the abdomen was unremarkable. Given the nondiagnostic work-up, liver biopsy was performed and pathology was consistent with glycogenic hepatopathy. She was referred to Endocrinology for improved glycemic control; however, liver enzymes normalized over the next several months despite minimal improvement in glycemic control. She was eventually transitioned to a closed-loop automated insulin delivery system and started dulaglutide for management of obesity. Subsequent A1c values significantly improved and liver enzymes remained within normal limits. Discussion: This case raises awareness of an under recognized complication of type 1 diabetes and challenges conventional thinking about factors leading to its resolution. Conclusion: Further investigation into the underlying pathophysiology of glycogenic hepatopathy is needed.